2018
DOI: 10.3390/ijerph15040745
|View full text |Cite
|
Sign up to set email alerts
|

The Emergency Medical System in Greece: Opening Aeolus’ Bag of Winds

Abstract: An Emergency Medical Service (EMS) system must encompass a spectrum of care, with dedicated pre-hospital and in-hospital medical facilities. It has to be organised in such a way as to include all necessary services—such as triage accurate initial assessment, prompt resuscitation, efficient management of emergency cases, and transport to definitive care. The global economic downturn has had a direct effect on the health sector and poses additional threats to the healthcare system. Greece is one of the hardest-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 31 publications
(179 reference statements)
1
43
0
Order By: Relevance
“…It was reported that Greek hospitals are struggling to meet the demands of both local people and migrants, mainly due to the lack of medical and human resources amid the economic crisis [10,16,17,18]. The health of refugees and migrants is jeopardized by barriers in access to Greek EMS [10,16,17,18].…”
Section: The Refugee Crisis Challenges the Greek Healthcare Systemmentioning
confidence: 99%
“…It was reported that Greek hospitals are struggling to meet the demands of both local people and migrants, mainly due to the lack of medical and human resources amid the economic crisis [10,16,17,18]. The health of refugees and migrants is jeopardized by barriers in access to Greek EMS [10,16,17,18].…”
Section: The Refugee Crisis Challenges the Greek Healthcare Systemmentioning
confidence: 99%
“…In particular there were higher overall caesarean rates for Sub-Saharan African, Somali and South Asian women; higher emer- [36]. This massive demographic and social change to Greece's country occurs at a time of severe economic crisis [37]. This has led to significant healthcare challenges for Greece's own citizens [38] [39] [40].…”
Section: Mode Of Obstetrical Deliverymentioning
confidence: 99%
“…However, Greece has been grappling with a severe socio-economic crisis since 2009 [1]. From the period 2015-2016, Greece experienced an unprecedented influx of refugees and migrants fleeing their home countries in the Middle East because of war, which created what is now known as the most massive displacement of a people since World War II [1,2]. The rapid entry of refugees into Greece raised the critical issue of health policy [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…From the period 2015-2016, Greece experienced an unprecedented influx of refugees and migrants fleeing their home countries in the Middle East because of war, which created what is now known as the most massive displacement of a people since World War II [1,2]. The rapid entry of refugees into Greece raised the critical issue of health policy [1,2]. The Greek National Health System (NHS) has been profoundly affected by the synergy of the economic and refugee crises leading to unmet needs for health care and subsequent adverse health outcomes for the local and refugee population [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation